Gender Differences in Mathematics and Integrated Science Achievement Among Junior Secondary School Students - Mathew Olagoke Ayodele (UUM Press, 2009)
Purpose - This study examined gender differences in Mathematics and Integrated Science achievement among the Junior Secondary School students with particular interest on the interaction effect of gender and school type on students' achievement.   Method - The study adopted an ex-post facto research design and generated data from an inventory from the statistics unit, Ministry of Education, Ado Ekiti, Nigeria Public Junior Secondary Schools (JSS). The inventory requested among other things, data on the Junior Secondary School Certifi cate Examinations (JSSCE) in Mathematics and Integrated Science over a two year period.   Findings - The study revealed that, signifi cant difference was detected in students' Science achievement; no signifi cant difference between male and female students in private and public schools; a strong interaction effect were detected between gender of the students, the type of school attended and achievement of students in Mathematics and Integrated Science; the average achievement gap of male and female students irrespective of the school type is statistically signifi cant in both Mathematics and Integrated Science, also, the strength of relationship between the gender of the students and the type of school attended is slightly stronger in Integrated Science than Mathematics.   Value - The possible implications for the study is discussed and addressed to the government and other stakeholders in education.